Assessing Effects of Large-Scale Land Transfers : Challenges and Opportunities in Malawi's Estate Sector - Deininger, Klaus; Xia, Fang (World Bank, Washington, DC, 2017)
This study uses data from the complete computerization of agricultural leases in Malawi, a georeferenced farm survey, and satellite imagery to document the opportunities and challenges of land-based investment in novel ways. Although 1.5 million hectares, or 25 percent, of Malawi's agricultural area is under agricultural estates, analysis shows that 70 percent has expired leases and 140,000 hectares are subject to overlapping claims. This reduces revenue from ground rent by up to US$35 millon per year or 5 percent of public spending and, by decreasing tenure security, may affect the productivity of land use. Indeed a 2006/07 survey shows large farms underperforming small ones in yield, productivity, and intensity of land use, while failing to generate positive spillovers. Recently passed Land Acts create opportunities to clarify the boundaries and lease status for existing estates as a first step toward systematic demarcation of customary estates. Failure to follow this sequence could exacerbate insecurity, with undesirable effects on productive performance.